Action Spectra for Guard Cell Rb(+) Uptake and Stomatal Opening in Vivia faba - Hsiao, Theodore C. (1973)
Abaxial epidermal strips, containing guard cells as the only viable cells, were prepared from leaves of Vicia faba following a period in darkness, and floated, under CO(2)-free air, on 2 mm RbCl + 0.1 mm CaCl(2) labeled with (86)Rb(+). Under white light (high pressure mercury vapor lamp), stomatal opening in these strips approached its maximum at less than 0.02 calorie per square centimeter per minute. Under light of different wavelengths, 20 nanometers apart, and at a low quantum flux density of 7 × 10(14) quanta per square centimeter per second, Rb(+) uptake and stomatal opening were activated only in the blue and long ultraviolet regions, with a peak at 420 to 460 nanometers. The action spectrum suggests that the underlying process is not photosynthesis. At higher quantum flux density (38 × 10(14) quanta per square centimeter per second), uptake and opening also responded to red (600-680 nanometers) and somewhat to green light, with a minimum at 540 to 560 nanometers, indicating a possible involvement of the photosynthetic process. This light-induced opening appeared not to be mediated by a lowering of CO(2) concentration, since CO(2)-free air was used in all treatments and controls. Stomatal opening paralleled Rb(+) uptake in all cases. This constitutes further evidence for the potassium transport hypothesis of stomatal movement. In the abaxial surface of leaf discs under air of normal CO(2) concentration, stomatal opening in white light approached its maximum at an intensity similar to that for epidermal strips. At both quantum flux densities, the action spectra for opening in leaf discs were very similar to those for epidermal strips. Thus, these light-linked processes for stomatal opening are likely to be the same in leaves as in epidermal strips.